2016
DOI: 10.3390/ph9030054
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Temozolomide-Loaded Nanoparticles for Glioblastoma Multiforme Targeting—Ideal Versus Reality

Abstract: Temozolomide (TMZ) is one of the most effective chemotherapeutic agents for glioblastoma multiforme, but the required high administration dose is accompanied by side effects. To overcome this problem and to further improve TMZ’s efficacy, targeted delivery of TMZ by using polymeric nanoparticles has been explored. We synthesised the PLGA-PEG-FOL copolymer and attempted encapsulation of TMZ into PLGA-PEG-FOL nanoparticles using the emulsion solvent evaporation method and the nanoprecipitation method. Conjugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Citrate-coated gold nanoparticles were synthetized as described in methods and subsequently two types of thiol PEGs (methylated and carboxylated) were chemisorbed on their surface. The methylated PEG contributes to the colloidal stabilization [45], while the carboxylated PEG permits conjugation with folic acid [43,46] following an EDC/NHS protocol. For the nanoparticles, a plasmonic peak of light absorption at 520 nm and an average size of 12 nm with a peak at 13 nm were observed by UV-visible spectroscopy and electron transmission microscopy, respectively (Fig.…”
Section: Synthesis and Characterization Of Aunp-peg-famentioning
confidence: 99%
“…Citrate-coated gold nanoparticles were synthetized as described in methods and subsequently two types of thiol PEGs (methylated and carboxylated) were chemisorbed on their surface. The methylated PEG contributes to the colloidal stabilization [45], while the carboxylated PEG permits conjugation with folic acid [43,46] following an EDC/NHS protocol. For the nanoparticles, a plasmonic peak of light absorption at 520 nm and an average size of 12 nm with a peak at 13 nm were observed by UV-visible spectroscopy and electron transmission microscopy, respectively (Fig.…”
Section: Synthesis and Characterization Of Aunp-peg-famentioning
confidence: 99%
“…Cur and coumarin-6 NPs were collected by centrifugation at 5,000 rpm for 30 minutes and washed three times in Milli-Q water. [21][22][23] TMAB-and Fab′-modified NPs were prepared using a postinsertion method. 24 TMAB and Fab′ were covalently attached to the outer membrane of the NPs prepared using the above method (Cur or coumarin-6 NPs) by thioether bonds formed by the reaction of maleimide with free sulfhydryl groups.…”
Section: Preparation Of Npsmentioning
confidence: 99%
“…To overcome this, Zhang et al saturated the aqueous emulsion phase with 0.5 wt/vol % of drug (i.e., 400 mg of drug per synthesis of a standard batch of particles), resulting in the use of a lot of drugs which can be very costly . Lee et al who tried altering different parameters of fabrication of nanoparticles using the emulsion solvent extraction/evaporation method were not successful at obtaining high entrapment efficiency and drug loading and thus, concluded that the emulsion solvent evaporation method of fabrication of TMZ‐loaded microparticles is not efficient and other method should be utilized to fabricate these particles . Ananta et al investigated different emulsion solvent extraction/evaporation techniques (i.e., single and double emulsion) for the fabrication of TMZ/PLGA nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…18 Lee et al who tried altering different parameters of fabrication of nanoparticles using the emulsion solvent extraction/evaporation method were not successful at obtaining high entrapment efficiency and drug loading and thus, concluded that the emulsion solvent evaporation method of fabrication of TMZ-loaded microparticles is not efficient and other method should be utilized to fabricate these particles. 28 Ananta et al investigated different emulsion solvent extraction/evaporation techniques (i.e., single and double emulsion) for the fabrication of TMZ/PLGA nanoparticles. They found that by using a single emulsion technique with TMZ saturation in the aqueous phase, they were able to increase loading efficiency by 90-700% and the encapsulation efficiency by 2-to 15-fold.…”
Section: Introductionmentioning
confidence: 99%